(untitled) (International Journal of Physiotherapy, 2019)
Background: Shoulder Impingement Syndrome (SIS) is a major contributing factor for shoulder pain. Although many therapists use Kinesio Taping (KT) and Manual Therapy (MT) for SIS, no such studies in combination with Supervised Exercise Therapy (SET) have been conducted in the context of Saudi Arabia. Thus, the purpose of this study is to compare the effectiveness of KT and MT with SET in patients with SIS. Methods: Randomized controlled trial. Thirty-two subjects were assigned into two groups (KT with SET and MT with SET). The following outcome measures were measured at baseline, three weeks and six weeks. The outcome measurements are pain intensity by a numerical pain rating scale (NPRS), Active range of motion in the shoulder (AROM) by goniometry, and the functions of the shoulder measured through Shoulder Pain and Disability Index (SPADI). A simple descriptive statistical analysis was adopted to describe the patient-specific demographic characteristics with respect to outcome parameters. Within-group and between groups comparison were analyzed using ANOVA, and Scheffes’ posthoc tests by using SPSS 21.0. Results: Sixteen subjects completed treatment in each group. No differences were identified between groups at baseline. In ANOVA, it was shown that both groups significantly (p<0.05) decreased pain intensity, improved function and increased shoulder AROM in the 3rd week, and 6th week. However, post hoc analysis results suggested that the KT, in conjunction with SET, had a higher proportion of change on 3rd week, of the pain intensity, SPADI, and AROM. Conclusion: KT with SET has been found to be more effective than the MT with SET in the 3rd week and had the same effect in the 6th week of the treatment. When an immediate effect is expected, KT may be a better choice of treatment in the management of SIS.